Spiritual Travel to Baitullah: Individual Piety in Global Capitalism - Dwi Santoso Ali Basyah; Zuly Qodir (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this paper explains critically related to one's journey to perform Hajj and Umrah (pilgrimage) concerning individual piety in the crowd (globalization and capitalization) of religious rituals. Hajj and Umrah are not only spiritual journeys that have personal ethical values. Hajj and Umrah can educate someone to be patient, calm, and more submissive to God. Hajj and Umrah also teach the perpetrators to be generous, have social sensitivity, and care with fellow human beings. The writing method in this paper is ethnographic-sociological. This paper's data is based on literature, observations, and interviews with pilgrims and Umrah from Indonesia in 2014 and 2018. This paper finds that the Hajj and Umrah are also closely related to the political economy problems administered by the state and the private sector, in addition to educating the perpetrators to be pious. Hajj and Umrah can thus be said to have two sides at once, namely individual piety and social class.